Biodiversity and quality of urban green landscape affect mental restorativeness of residents in Multan, Pakistan - Rehman, Zainab; Zubair, Muhammad; Hafiz, Dalia Osama; Manzoor, Syed Amir (Frontiers in Sustainable Cities, 2024)
Introduction The influence of urban green spaces on public health is receiving unprecedented attention. Managing urban greenspaces sustainably requires an understanding of the mechanisms behind the positive effects of urban biodiversity on the wellbeing of residents. Urban parks could improve mental restoration of park users. The restoration potential may be influenced by the biophysical characteristics of the park. Methods This study aimed to understand two aspects of urban parks in Multan, Pakistan: (a) How does the perception of biodiversity and the quality of urban parks relate to mental restorativeness of park visitors? (b) What are the determinants of respondents' willingness to pay for the conservation and management of park biodiversity and quality in urban parks? Data were collected from October 2021 to December 2021 through a cross-sectional survey in which 550 park visitors were interviewed from six randomly selected urban parks in Multan. Multiple linear regression analysis, a binary logistic model, and a chi-square test were applied to analyze the data. Results and discussion The study empirically highlights the positive contribution of park visits to mental restorativeness. Biodiversity and quality were positively correlated with the mental restorativeness of park visitors. Sixty-two percent (62%) of the visitors were reluctant to pay, whereas 38% were ready to pay between Rs. 850/3.7 and Rs. 1,700/7.4 each year. Education, occupation, and monthly income significantly positively affected the respondent's WTP attitudes. The study highlights the importance of using urban parks as tools to promote mental restorativeness, combat social stress, and increase urban vegetation cover.